2016
DOI: 10.52763/pjsir.phys.sci.59.3.2016.157.166
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Quality in Urban Areas of Pakistan: A Case Study of Gujranwala City

Abstract: A study was conducted to evaluate the drinking water quality of Gujranwala city. Samples were collected from 16 locations including: 4 tube wells, 4 overhead reservoirs (OHR) and 8 house connections. Twelve physicochemical and two bacteriological parameters were tested, before and after monsoon and compared with National Standards for Drinking Water Quality (NSDWQ). The results demonstrated that most of the physicochemical parameters, except lead, nickle and chromium were within NSDWQ before and after monsoon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
2
15
0
Order By: Relevance
“…All these and other were confirmed from various stages ( Raw , Filtrate , Treat, Net ).The results clearly indicated that chlorination is efficient against the bacteria in water , drinking water must be free some components which may affect the human health . Such component include minerals, organic substances and pathogenic microorganisms (Haydar et al , 2009).…”
Section: Ivdiscussionmentioning
confidence: 99%
“…All these and other were confirmed from various stages ( Raw , Filtrate , Treat, Net ).The results clearly indicated that chlorination is efficient against the bacteria in water , drinking water must be free some components which may affect the human health . Such component include minerals, organic substances and pathogenic microorganisms (Haydar et al , 2009).…”
Section: Ivdiscussionmentioning
confidence: 99%
“…In terms of fecal coliforms, 50% of the samples before the rainy season and 75% of the samples in the rainy season showed coliform pollution (Haydar et al, 2009).…”
Section: Comparative Analysismentioning
confidence: 99%
“…Generally, high pH value causes corrosion of metallic pipes which is associated with serious health problems due to the presence of heavy metals in drinking water leached inside the pipe distribution systems through which it passes. WHO guidelines [16] recommend a desirable limit of 6.5 to 8.0 for the pH of drinking water [17]. A little variation from this range is usually not associated to health issues but the value ranging from 10 to 12.5 have been documented to cause swelling of hair fibers and skin problems, and stomach disorders.…”
Section: Phmentioning
confidence: 99%